OP0139 Regulation of cd154 in systemic lupus erythematosus. (1st June 2001) - Cron, RQ; Genin, A; Brunner, M
Abstract : CD40-ligand (CD154) is expressed on the surface of activated CD4 T cells and as a soluble cytokine. CD154 is a critical regulator of the immune response via its interaction with CD40 on various cell types, and, therefore, it is not surprising that its expression is tightly controlled. Current reports have described abnormal expression (increased and prolonged levels) of CD154 in adult patients with systemic lupus erythematosus (SLE), similar to observations in lupus-prone mice. We have recently confirmed these findings in paediatric SLE patients. Normally, like several tumour necrosis factor cytokine family members, CD154 expression is primarily controlled at the level of gene transcription and mRNA stability. Moreover, regulatory defects in intracellular signalling pathways that may effect cytokine mRNA levels have recently been described in CD4 T cells from patients with SLE. Using real-time quantitative PCR we have found that CD154 mRNA levels are increased in SLE patients versus matched controls. Preliminary results from nuclear run-on assays also suggest that increased CD154 transcription plays a role in CD154 hyper-expression in SLE. The CD154 cis -element (s) responsible for this increase in transcription is unknown. Although we had previously identified a relatively weak proximal 5′ flank transcriptional promoter, very little is known about the cis- and trans -regulatory elements that contribute to CD154 gene expression. We have recently identified a NFκB-responsive transcriptional enhancer element located within and just downstream of the 3′ CD154 untranslated region. Moreover, using nuclei from primary human CD4 T cells, we have identified a novel DNase I hypersensitive site located approximately 1 kb upstream of the proximal promoter. This novel site is flanked by several potential T cell transcription factor binding sites and, thus, may function as a transcriptional enhancer. We are currently comparing the transcriptional activities of these various CD154 cis -regulatory elements in T cells from SLE patients and controls in order to identify region (s) that contribute to enhanced CD154 expression in SLE. Ultimately, we hope to be able to target the cis - or trans -regulatory elements that lead to the abnormal expression of CD154 in SLE and various other autoimmune disorders.